2016
DOI: 10.1647/2015122
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Vasculopathy and Retinal Detachment in a Bald Eagle (Haliaeetus leucocephalus) With Lead Toxicosis

Abstract: A subadult male bald eagle ( Haliaeetus leucocephalus ) was presented for severe depression and weakness. Physical examination findings included depressed mentation, dehydration, sternal recumbency, poor body condition, and bilateral, whole-head, horizontal nystagmus. A heavy-metal panel was performed, and blood lead levels were 6.1 ppm. Treatment for lead poisoning was initiated, including subcutaneous fluids and parenteral calcium-disodium ethylenediaminetetraacetic acid, ceftiofur, and meloxicam. Ophthalmic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…Several recent studies have reported sub-lethal effects of lead in wild birds, supplementing earlier research. A histopathological study of the eyes of a bald eagle provided the first evidence of ocular lesions associated with sub-lethal but extremely elevated blood lead levels (c. 610 µg/dl—Eid et al 2016). The prognosis for this rehabilitated bird’s vision was too poor for it to be released back to the wild.…”
Section: Impacts Of Lead Poisoning On Wildlifementioning
confidence: 99%
“…Several recent studies have reported sub-lethal effects of lead in wild birds, supplementing earlier research. A histopathological study of the eyes of a bald eagle provided the first evidence of ocular lesions associated with sub-lethal but extremely elevated blood lead levels (c. 610 µg/dl—Eid et al 2016). The prognosis for this rehabilitated bird’s vision was too poor for it to be released back to the wild.…”
Section: Impacts Of Lead Poisoning On Wildlifementioning
confidence: 99%
“…A multisystemic fibrinoid necrosis of arterioles has previously been described in a bald eagle with lead toxicity. 8 It is unknown whether the preferred involvement of cardiac, neural, and ocular arteries in the current study may indicate an increased sensitivity of these vessels to lead. This selective vascular injury does not appear to be directly associated with the amount of blood flow, as renal arterioles would be expected to be frequently affected if that were the case.…”
Section: Discussionmentioning
confidence: 77%
“…With the exception of 1 previous study ( n = 484 bald eagles), 11 reports of lead intoxication–associated lesions in bald eagles have otherwise been limited to small case numbers ( n = 1–6). 6,8,13,23,29…”
Section: Discussionmentioning
confidence: 99%
“…Structural detail of the pecten oculi has been elucidated in anatomical studies using scanning electron and light microscopy . However, advanced diagnostic imaging investigations (ie, optical coherence tomography—OCT) may better help to understand the precise role of the pecten oculi in normal ocular health and in disease pathogenesis . Ultrasonography (US) is a widely available, quick, and noninvasive imaging technique with multiple modalities (eg, color and pulsed Doppler ultrasonography; D‐US) that has been successfully used to investigate the pecten oculi .…”
Section: Introductionmentioning
confidence: 99%
“…10,15,22,23 However, advanced diagnostic imaging investigations (ie, optical coherence tomography-OCT) may better help to understand the precise role of the pecten oculi in normal ocular health and in disease pathogenesis. [24][25][26][27] Ultrasonography (US) is a widely available, quick, and noninvasive imaging technique with multiple modalities (eg, color and pulsed Doppler ultrasonography; D-US) that has been successfully used to investigate the pecten oculi. 7,8,28 Physiologic parameters for resistive and pulsatility indexes of the pectinate artery have been investigated using D-US in both American Pekin ducks (Anas platyrhynchos domestica) and harpy eagles (Harpia harpyja).…”
Section: Introductionmentioning
confidence: 99%